State crime, the prophetic voice and public criminology activism - Kramer, Ronald C. (Critical criminology, 2016)
State crimes are, by far, the most destructive of all crimes. The use and threat to use nuclear weapons, the aerial bombardment of civilians, wars of aggression, torture, the failure to mitigate global warming and adapt to climate change ecocide, along with myriad other state-corporate crimes, fill the world with death and devastation, misery and want. This article argues that criminologists have a responsibility to act as public criminologists by speaking in the "prophetic voice" concerning these crimes and their victims, and then acting in the political arena in an attempt to control and prevent these harms. The paper briefly describes three approaches to engaging in what Belknap (Criminology 53:1-23, 2015) calls "criminology activism" on these issues. The first approach is for criminologists to counter the cultures of denial and normalization that usually cover state crimes. The second involves contesting the global corporate capitalist system and the power of the American capitalist state in an effort to achieve specific progressive policy reforms and structural changes in the global political economy. Finally, criminologists can work to enhance the democratization of the international political community and strengthen the ability of specific international legal institutions to control state crimes.